Synthesis of vertically aligned carbon nanotubes using natural palm oil as carbon precursor - Suriani, A.B.; Azira, A.A.; Nik, S.F.; Nor, R.M.; Rusop, M. (2009)
Vertically aligned carbon nanotubes (VACNTs) have been synthesized on silicon substrates in a thermal catalytic chemical vapor reactor using natural palm oil as the carbon source. Field Emission Scanning Electron Microscopy (FESEM) and microraman analysis revealed dense bundles of mixed multi-walled and single-walled carbon nanotubes (CNTs). The diameters of the single-walled carbon nanotubes (SWCNTs) were estimated to be between 0.6 nm and 1.2 nm. Thermogravimetric analysis (TGA) results showed that 90 purity was achieved at the expense of 4 weight catalyst material. (C) 2009 Elsevier B.V. All rights reserved.